UPAYA HUKUM WAJIB PAJAK BADAN TERHADAP HASIL PEMERIKSAAN PAJAK - EVELYN EVELYN (PREMISE LAW JURNAL, 2014)
ABSTRACT Tax collection system in Indonesia adopts self-assessment system in which the taxpayers are give full trust to calculate, consider and pay for the tax due themselves in accordance with tax legislation.Tax audit was not done to all of corporate taxpayers, but only the disobedient corporate taxpayers who are against the stipulation of tax legislation. After being audited, the Directorate General of Tax shall notify the result of audit through the letter of audit result notification (SPHP) and give the right to the corporate tax payers to attend the closing conference, then issue a legal product in the form of Tax Assessement Letter. In case of untrue Letter of Tax Assessment, the corporate taxpayers may apply for a legal remedy as the legal protection in seeking justice for corporate lawyers. Keywords: Legal Remedy, Corporate Taxpayers, Tax Audit